Rheumatoid arthritis and sexuality: A patient survey in France - Kobelt, Gisela (BioMed Central, 2012)
BACKGROUND: The objective of this study was to evaluate the impact of rheumatoid arthritis (RA) on patients’ sexuality and identify disease and other factors such as fatigue that most influence sexual relationships. METHODS: A specific pretested questionnaire was sent to all members of a French patient association (ANDAR). Questions related to demographics, disease status, quality of life (utility, EQ-5D), pain, psychological status (mood), fatigue and emotional and sexual relationships. To isolate the impact of RA, an attempt was made to include a matched sample from the general population. RESULTS: The analysis included 1271 patients, but only 70 controls agreed to participate and comparisons should therefore be considered with caution. The two groups were similar in terms of age, gender distribution, living conditions and diseases other than RA. However, patients scored worse for global health, mood, fatigue, had a lower utility (0.55 versus 0.65). Controls were more active sexually (69% versus 63%), in particular women (71% versus 60%). Age, gender, living alone, physical function and mood were significant predictors for being sexually active for patients; for controls, age and overall quality of life (utility) were significant predictors. CONCLUSIONS: While it is known that RA has a negative impact on patients’ sexuality, there have been few attempts to quantify the problem. Our study highlights the negative impact of RA on patients’ sexuality, and triggers the question how to include this aspect into care.